Increased degradation of FMRP contributes to neuronal hyperexcitability in tuberous sclerosis complex - Kellen D. Winden; Truc T. Pham; Nicole A. Teaney; Juan Ruiz; Ryan Chen; Cidi Chen; Mustafa Sahin (Cell Reports, 2023)
Summary: Autism spectrum disorder (ASD) is a highly prevalent neurodevelopmental disorder, but new therapies have been impeded by a lack of understanding of the pathological mechanisms. Tuberous sclerosis complex (TSC) and fragile X syndrome are associated with alterations in the mechanistic target of rapamycin (mTOR) and fragile X messenger ribonucleoprotein 1 (FMRP), which have been implicated in the development of ASD. Previously, we observed that transcripts associated with FMRP were down-regulated in TSC2-deficient neurons. In this study, we find that FMRP turnover is dysregulated in TSC2-deficient rodent primary neurons and human induced pluripotent stem cell (iPSC)-derived neurons and is dependent on the E3 ubiquitin ligase anaphase-promoting complex. We also demonstrate that overexpression of FMRP can partially rescue hyperexcitability in TSC2-deficient iPSC-derived neurons. These data indicate that FMRP dysregulation represents an important pathological mechanism in the development of abnormal neuronal activity in TSC and illustrate a molecular convergence between these two neurogenetic disorders.